2014
DOI: 10.1016/j.heares.2014.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Tinnitus-related dissociation between cortical and subcortical neural activity in humans with mild to moderate sensorineural hearing loss

Abstract: Tinnitus is a phantom sound percept that is strongly associated with peripheral hearing loss. However, only a fraction of hearing-impaired subjects develops tinnitus. This may be based on differences in the function of the brain between those subjects that develop tinnitus and those that do not. In this study, cortical and sub-cortical sound-evoked brain responses in 34 hearing-impaired chronic tinnitus patients and 19 hearing level-matched controls were studied using 3-T functional magnetic resonance imaging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
77
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(94 citation statements)
references
References 59 publications
17
77
0
Order By: Relevance
“…Our results are consistent with recent auditory stimulusbased fMRI findings in which reduced functional connectivity was observed between the thalamus (MGB) and the cortex of tinnitus patients [14,15]. Our findings may be considered in the context of model of Rauschecker et al in which the projections of the nucleus accumbens feed back to the thalamic reticular nucleus, which in turn selectively inhibits sections of the thalamus and auditory cortex corresponding to the tinnitus pitch.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results are consistent with recent auditory stimulusbased fMRI findings in which reduced functional connectivity was observed between the thalamus (MGB) and the cortex of tinnitus patients [14,15]. Our findings may be considered in the context of model of Rauschecker et al in which the projections of the nucleus accumbens feed back to the thalamic reticular nucleus, which in turn selectively inhibits sections of the thalamus and auditory cortex corresponding to the tinnitus pitch.…”
Section: Discussionsupporting
confidence: 92%
“…The thalamus, which regulates the flow of sensory information to and from the auditory cortex, is thought to play an important role in the perception of tinnitus [9,14]. Consistent with this view, we observed that the thalamus showed decreased functional connectivity with the primary and associative auditory cortex, specifically the STG (Brodmann's area 42) and MTG (Brodmann's area 21).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…One widely cited neural synchrony model of tinnitus has attributed oscillatory activity in the TFR to hyperpolarization of thalamic nuclei consequent on deafferentation of auditory pathways (Llin as et al, 2005;Kalappa et al, 2014). Hyperpolarization could explain reduced sound-evoked functional connectivity between auditory cortical and subcortical structures which has been reported in tinnitus sufferers compared to controls (Boyen et al, 2014;Lanting et al, 2014).…”
Section: Other Electrophysiological Responses In Tinnitus and Rimentioning
confidence: 99%
“…This suggests that some pathologies are more likely to be associated with tinnitus than others; for example, 74-91% of otosclerosis patients report tinnitus [Ayache et al, 2003;Sobrinho et al, 2004]. Alternatively, perception of tinnitus has been hypothesized to be due to a failure of the 'thalamic gate' [Boyen et al, 2014;Rauschecker et al, 2010].…”
Section: Evidence Of Abnormal Neural Gain In Tinnitus and Hyperacusismentioning
confidence: 99%